PENDIDIKAN ISLAM DALAM PEMBERDAYAAN MASYARAKAT LANJUT USIA - Ni'mah, Siti Jaroyatun; Nurhuda, Abid; Al Fajri, Muhammad (Fitrah, 2024)
Islamic education aims to build quality humans both in this world and in the afterlife. Apart from that, he must also take part in empowering the community to create prosperity and happiness among them. One of the groups that must be empowered is the elderly community, where they experiences decline and change from a psychological and physiological perspective. This research aims to describe Islamic education in empowering elderly communities. The method used is qualitative with a library study approach model. The data was collected using documentation techniques and then analyzed descriptively. The research results show that Islamic education has a very important role in bridging understanding of religion, forming morals, creating a sense of mutual assistance, and helping to prepare complete Muslim individuals for the daily life of elderly people. Apart from that, it is also possible to achieve physical and spiritual well-being as well as happiness in old age through various religious programs such as holding Islamic Recitations, Al-Qur'an Reading Guidance, Worship Development, and Hadroh Training.